2015
DOI: 10.1115/1.4029879
|View full text |Cite
|
Sign up to set email alerts
|

Blockage Effects From Simulated Thermal Barrier Coatings for Cylindrical and Shaped Cooling Holes

Abstract: Film cooling and sprayed thermal barrier coatings (TBCs) protect gas turbine components from the hot combustion gas temperatures. As gas turbine designers pursue higher turbine inlet temperatures, film cooling and TBCs are critical in protecting the durability of turbomachinery hardware. One obstacle to the synergy of these technologies is that TBC coatings can block cooling holes when applied to the components, causing a decrease in the film cooling flow area thereby reducing coolant flow for a given pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also shown on Fig. 4 is data from Whitfield et al [30] who examined C d for a larger-scale, smooth film cooling hole of the same shape in a low-speed wind tunnel. Theirs is the only paper that has previously characterized flow through this hole shape.…”
Section: Resultsmentioning
confidence: 99%
“…Also shown on Fig. 4 is data from Whitfield et al [30] who examined C d for a larger-scale, smooth film cooling hole of the same shape in a low-speed wind tunnel. Theirs is the only paper that has previously characterized flow through this hole shape.…”
Section: Resultsmentioning
confidence: 99%
“…Ronald et al [15] indicated that in comparison with cylindrical holes, shaped holes can better resistant to partial holeblockage. Christopher et al [16] blocked film holes with a low conductivity material to simulate the partial blockage of cylindrical and shaped holes caused by TBC spallation. Their experiment indicated that at low BRs, the blockages of shaped hole have very little effect on adiabatic film effectiveness, but at high BRs, the film effectiveness of shaped and cylindrical holes was decreased about 75% by hole-blockage.…”
Section: Introductionmentioning
confidence: 99%